Ambient Temperature Stable, Scalable COVID‐19 Polymer Particle Vaccines Induce Protective Immunity (Adv. Healthcare Mater. 3/2022). Issue 3 (2nd February 2022) - Chen, Shuxiong; Evert, Benjamin; Adeniyi, Adetayo; Salla‐Martret, Mercè; Lua, Linda H.‐L.; Ozberk, Victoria; Pandey, Manisha; Good, Michael F.; Suhrbier, Andreas; Halfmann, Peter; Kawaoka, Yoshihiro; Rehm, Bernd H. A.
Abstract : Sars‐CoV‐2 Vaccines In article number 2102089 by Bernd H. A. Rehm and co‐workers, an ambient temperature‐stable, scalable COVID‐19 polymer particle vaccines are developed by engineering endotoxinfree bacterial cell factories to self‐assemble biopolymer particles coated with immunogenic SARS‐CoV‐2 antigens. Polymer particle vaccines induce protective immunity in a hamster SARS‐CoV‐2 infection model reducing virus titers up to viral clearance in lungs post infection.